2005
DOI: 10.1631/jzus.2005.b0885
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of mycophenolic acid in Chinese kidney transplant patients

Abstract: Abstract:To assess the influence of cyclosporin A (CsA) and tacrolimus (FK506) on mycophenolic acid (MPA) and correlation analysis of the pharmacokinetic parameters and patient characteristics, clinical outcome in Chinese kidney transplant recipients, the pharmacokinetics of 1000 mg mycophenolate mofetil (MMF) twice daily was measured by high-performance liquid chromatography (HPLC). PKS (Pharmaceutical Kinetics Software) 1.0.2 software package was used for the calculation of pharmacokinetic parameters. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…The value of MPA CL/F is very close to that of the present study, indicating that there may be no pronounced ethnicity difference in MPA CL/ F . This result is also consistent with previous observations in Chinese [43–46] and Korean [47] renal transplant patients. In terms of MPAG CL/ F , the typical value of healthy Chinese was 46% higher than that of stable White renal transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The value of MPA CL/F is very close to that of the present study, indicating that there may be no pronounced ethnicity difference in MPA CL/ F . This result is also consistent with previous observations in Chinese [43–46] and Korean [47] renal transplant patients. In terms of MPAG CL/ F , the typical value of healthy Chinese was 46% higher than that of stable White renal transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
“…CL/F of MPA and MPAG were reported to be 0.158 l h -1 kg -1 and 0.0144 l h -1 kg -1 , respectively, in patients on tacrolimus, which does not influence the EHC of MPA [40][41][42]. The value of MPA CL/F is very close to that of the present study, indicating that there may be no pronounced ethnicity difference in MPA CL/F.This result is also consistent with previous observations in Chinese [43][44][45][46] and Korean [47] renal transplant patients. In terms of MPAG CL/F, the typical value of healthy Chinese was 46% higher than that of stable White renal transplant recipients.…”
Section: Discussionsupporting
confidence: 92%
“…We previously compared mean MPA AUC 0–12 h of MMF combined with CsA or Tac in 29 patients at day 7 after kidney transplantation: MPA AUC 0–12 h in the Tac group was statistically higher (60.9467 ± 11.6779 μg h/ml) than that in the CsA group (48.184 ± 10.6598 μg h/ml) (p = 0.004) . The present study obtained similar results: MPA C 0 and MPA AUC 0–12 h in the Tac group were significantly higher than in the CsA group (77.535 ± 33.615 μg h/ml vs. 59.463 ± 16.252 μg h/ml, respectively) (p = 0.002).…”
Section: Discussionsupporting
confidence: 81%
“…5,[8][9][10] Pharmacokinetic parameters may differ between races. Lu et al 11 studied the pharmacokinetics of MPA in 29 Chinese cases 10 days after renal transplantation, finding that, although concentration-time profiles were similar to those of white, African American, and Korean patients, there were some differences in C max , t max , and AUC 0-12h . Clinical research in Asian renal transplant recipients found that the MPA-AUC 0-12h values of patients in a stable state were significantly lower than the therapeutic window range of 30-60 mg$h$L 21 .…”
Section: Introductionmentioning
confidence: 99%